(untitled) (Research, Society and Development, 2022)
Objective: To measure the prevalence of depression, anxiety and stress levels in a university community during the COVID-19 pandemic. Methods: A cross-sectional exploratory-descriptive study was implemented in two stages, in the initial and middle stages of the COVID-19 pandemic in Brazil, with a sample of a university community in emergency remote learning. Results: The prevalence of high scores (Extremely severe) for depression, anxiety and stress, respectively, were 27.34 (25.30-29.47), 27.12 (25.08-29.25) and 19.38 (17.59-21.30) in the initial stage and 25.79 (24.11-27.82), 26.01 (24.33-28.05) and 17.18 (15.76-18.98) in the middle stage of the pandemic. Conclusions: The prevalence of high scores for the screened psychological disorders were high in both stages of the pandemic. We recommend preventive and care actions for the university community in periods of crisis such as the pandemic. Future studies can look at the trend in prevalence rates over time as social distancing measures, the pandemic and emergency remote learning are slowing down.